KEPEMIMPINAN: SUATU TELAAH KRITIS PUSTAKA - Cahya Purnama Asri; Mugi Harsono (JURNAL ILMIAH EDUNOMIKA, 2024)
Leadership is an important aspect of the managerial function, which aims to motivate members of the organization to carry out their work effectively. Power is required in leadership to influence and motivate subordinates. Effective leadership is tailored to each situation, and issues such as the task being performed and the dynamics of subordinates must be considered and power is linked to leadership, and every leader needs the ability to influence and motivate subordinates. This study aims to determine the determinants of leadership. The method used was systematic literature review, and used 16 research articles as review materials. The results showed several determinants of leadership. This study did not find leadership as a mediating or moderating variable. Keywords: leadership, organization, literature review, determinant